Corticotrophin-Releasing Factor Modulates the Facial Stimulation-Evoked Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission in vivo in Mice - Wu, Wen-Yuan; Liu, Yang; Wu, Mao-Cheng; Wang, Hong-Wei; Chu, Chun-Ping; Jin, Hua; Li, Yu-Zi; Qiu, De-Lai (Frontiers in Cellular Neuroscience, 2020)
Corticotropin-releasing factor (CRF) is an important neuromodulator in central nervous system that modulates neuronal activity via its receptors during stress responses. In cerebellar cortex, CRF modulates the simple spike firing activity of Purkinje cells (PCs) has been previously demonstrated, while the effect of CRF on the molecular layer interneuron (MLI)-PC synaptic transmission is still unknown. In this study, we examined the effect of CRF on the facial stimulation-evoked cerebellar cortical MLI-PC synaptic transmission in urethane-anesthetized mice by in vivo cell-attached recording, neurobiotin juxtacellular labeling, imunohistochemistry techniques and pharmacological method. Cell-attached recordings from cerebellar PCs showed that air-puff stimulation of ipsilateral whisker pad evoked a sequence of tiny parallel fiber volley (N1) followed by MLI-PC synaptic transmission (P1). Micro-application of CRF in cerebellar cortical molecular layer induced increases in amplitude of P1 and pause of simple spike firing. The CRF decreases in amplitude of P1 waveform was in a dose-dependent manner with the EC50 of 241 nM. The effects of CRF on amplitude of P1 and pause of simple spike firing were abolished by either a nonselective CRF receptor antagonist, α-helical CRF-(9-14), or a selective CRF-R1 antagonist, BMS-763534 (BMS, 200 nM), but were not prevented by a selective CRF-R2 antagonist, antisauvagine-30 (200 nM). Notably, application CRF not only induced a significant increase in spontaneous spike firing rate, but also produced a significant increase in the number of the facial stimulation-evoked action potential in molecular layer interneurons (MLIs). The effect of CRF on the activity of MLIs was blocked by the selective CRF-R1 antagonist, and the MLIs expressed the CRF-R1 imunoreactivity. These results indicate that CRF increases excitability of MLIs via CRF-R1, resulting in an enhancement of the facial stimulation-evoked MLI-PC synaptic transmission in vivo in mice.